Losses of Foliage to Defoliating Insects Increase with Leaf Damage Diversity Due to the Complementarity Effect - Kozlov, Mikhail V.; Zverev, Vitali (MDPI AG, 2025)
The functioning of ecosystems critically depends on biodiversity. However, the effects of herbivore diversity on plant damage caused by herbivore feeding remain underexplored. In this study, we tested the prediction that relative losses of foliage to defoliating insects increase with leaf damage diversity (LDD), and we also explored the mechanisms underlying the observed LDD patterns. We measured insect herbivory in 501 individuals of three deciduous woody species (Betula pubescens, Salix phylicifolia, and Vaccinium uliginosum) across 38 localities in north-western Russia, collected 8844 leaves damaged by defoliating insects, classifying the 21,073 feeding events observed in these leaves into 29 damage types. Overall, LDD significantly decreased with increasing latitude but showed no variation along elevation or pollution gradients. Herbivory weakly but significantly increased with increasing LDD, and a strong positive correlation between the rarefied number of leaf damage types and their evenness provided evidence for the complementarity effect underlying this herbivory increase, indicating that insects producing different leaf damage types differ in their resource use.